The Role of Madrasah Principal in Teacher Performance Supervision - Lukman Hakim (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to obtain in-depth information related to the role of school principals in supervising teacher performance. Supervised performance is related to teaching and learning activities. The principal carries out supervision to improve the quality of teacher performance. This study used a qualitative approach with a survey method. Data were collected using observation, interviews, and documentation. Data analysis consists of the data reduction process, data presentation, conclusion drawing, and triangulation. The findings show that supervision activities by school principals have provided valuable input for teachers to improve the quality of education. The teacher has carried out teaching and learning activities that are adapted to current conditions. However, the identified shortcomings are in the mastery of digital technology devices as a tool that can support educational activities.